Firm Diversification and Performance: An Empirical Examination - Mota, Jorge Humberto (2020)
This paper examines several dimensions of the relationship between diversification and performance. Specifically, we investigate the link between related and unrelated diversification and performance. We also study the effect of the potential redeployment of ‘plastic’ assets on unrelated diversification. To investigate this, we estimated a dynamic panel on a data set of 2,396 diversified firms from the euro area, over the 2010-2017 sampling period. Empirical results indicate that an increase in the level of unrelated diversification, is significantly associated with an 0.65 percent improvement in performance, and related diversification with an 0.98 percent increase in performance. Additionally, we found that the level of unrelated diversification is positively and significantly impacted, 1.32 percent, by changes in the level of asset plasticity. Overall, our findings contribute to the corporate diversification literature by documenting that both, related and unrelated diversification, impact positively performance. Moreover, providing evidence consistent with the intuition that asset plasticity may be a positive factor for unrelated diversification strategies.